Agreement between Subjective Global Nutritional Assessment and the nutritional assessment of the World Health Organization - Pimenta,Fabiana S. (2018)
Abstract Objective: To assess the agreement between the results of the Subjective Global Nutritional Assessment questionnaire, adapted for children and adolescents of the Brazilian population, and the nutritional status assessment method through growth curves and the classification of the World Health Organization in a pediatric hospital service. Methods: This was an analytical, quantitative, cross-sectional study. During the data collection period, the nutritional status of all patients from 0 to 12 years of age, admitted to the pediatric unit of a university hospital, was concomitantly assessed according to the Subjective Global Nutritional Assessment and World Health Organization curves. To determine the assessment and agreement between these methods, the Kappa and Kendall coefficients were used, respectively, considering a significance level of 5%. Results: Sixty-one children participated, with a predominance of males. It was observed that the highest frequency of equivalent results occurred among the group classified as well nourished, and that only the height/age variable showed a close agreement between the methods. Additionally, there was a good correlation only for the weight/height variable between the assessment tools used. Conclusion: Due to the low agreement between the methods, the combination of both may be beneficial for the nutritional assessment of pediatric patients, collaborating with the early diagnosis of nutritional alterations and facilitating the use of adequate dietary therapy.